浅析元朝与高丽的联姻关系 = Analysis of the political marriage between Yuan dynasty and Koryo - 杨义芳 Jong, Ellen Yi Fang (2019)
918年，王建以开城为中心建立了高丽王朝，先后消灭新罗、百济，于 936年统一了朝鲜半岛。13世纪初，成吉思汗统一蒙古各部后，于1206年建立了 强大的大蒙古帝国，随后蒙古铁骑在欧亚大陆驰骋，展现了蒙古想要统治世界 的强大野心。其铁骑所到之处，为欧亚各国带来了严峻考验，位于朝鲜半岛上 的高丽王朝，也面临了蒙古的威胁。本篇文章将以元高联姻为中心点，探讨元 朝公主在这中间所扮演的角色、高丽又是如何通过与元朝的联姻来提升自己的 地位，以及元高联姻之后高丽王室的蒙古化。At the beginning of the 13th century, after Genghis Khan unified the various Mongolian ministries, the powerful Great Mongolian Empire was then established in 1206. The Mongolian army galloped in the Eurasian continent, demonstrating their ambition of ruling the world. Wherever their army reached, there came disasters to the other Eurasian countries. The Koryo on the Korean peninsula also faced the threat of Mongolia. This article will focus on the marriage relationship of Yuan Dynasty and Koryo, explored the role played by the Princess of the Yuan Dynasty, and how Koryo has improved his status through the marriage with Yuan Dynasty, lastly the mongolianization of the Koryo royal family after the political marriage.